Yersinia arthritis: a clinical, immunological, and family study of 2 cases. Issue 2 (April 1982) - Sheldon, P J; Mair, N S; Fox, E
Abstract : We describe 2 patients who presented with yersinia arthritis within a period of 5 months in Leicester. Both were HLA B27 positive. Arthritis followed 2 to 3 weeks after pneumonia, abdominal pain, dysuria, and evidence of hepatic involvement in the first case, and dysuria and conjunctivitis in the second. Immunological studies showed the presence of IgM, IgG, and IgA antibodies at a significant level against Yersinia enterocolitica serotype O:3 in serum and synovial fluid, and immune complexes in the serum of the first case and synovial fluid of both. Arthropathy resolved after 16 weeks in the first case and 12 weeks in the second, the latter requiring systemic corticosteroids. Family studies revealed psoriatic spondylarthritis in the brother, and bilateral sacroiliitis in the mother of the second case. Both were HLA B27 positive. These are the fourth and fifth reported cases of yersinia arthritis in Britain. We believe the condition is probably underdiagnosed and that yersiniosis should be considered as a possibility in otherwise unexplained arthritis.